Liposome-mediated IL-28 and IL-29 expression in A549 cells and antiviral effect of IL-28 and IL-29 on WISH cells - Li Ming-cai; Wang Hao-yang; Wang Hai-yan; Li Tao; He Shao-heng (Acta Pharmacologica Sinica, 2016)
Aim: To construct the recombinant vectors carrying interleukin (IL)-28A, IL-28B and IL-29 cDNAs and express them in human A549 cells, and analyze their antiviral activity in vesicular stomatitis virus (VSV)-infected human immortalized amnion epithelial cell line (WISH cells). Methods: Total cell RNA was extracted from human peripheral blood mononuclear cells (PBMC) activated with poly I:C. The cDNAs encoding human IL-28A, IL-28B, and IL-29 were amplified by reversetranscription polymerase chain reaction (RT-PCR) and inserted into pcDNA3.1/ V5-His-TOPO vectors. These recombinant vectors were transfected into human A549 cells by a liposome-mediated gene transfer method. Semiquantitative RTPCR and Western blotting were used to detect the mRNA and protein expression of IL-28A, IL-28B, and IL-29. The antiviral activity of IL-28A, IL-28B, and IL-29 was determined by a cytopathic effect reduction assay on WISH cells using VSV as a challenge virus. Results: The DNA sequences of the inserts were identical to the published sequences encoding IL-28A, IL-28B, and IL-29 in GenBank. It was demonstrated that IL-28A, IL-28B, and IL-29 genes were markedly transcribed in transfected cells. Expression of all 3 interleukins in A549 cells was confirmed by Western blot analysis. IL-28 and IL-29 expressed by A549 cells, like interferon (IFN) α-2b, were able to protect WISH cells against VSV infection. Conclusion: IL-28 and IL-29 cDNAs were successfully cloned and expressed in eukaryotic cells via transfection with pcDNA3.1/V5-His-TOPO-IL-28/IL-29. Transfection with this vector produced a specific antiviral activity similar to that of IFN-α, which will provide a new tool for the functional study of these cytokines in humans.